The System of Declension in the Colophons of Armenian Manuscripts of the XV Century - HARUTYUNYAN, KHACHIK (Bulletin of Yerevan University B: Philology, 2021)
The present article investigates the features of the declension system in the colophons of Armenian manuscripts of the 15thcentury. The aim of this study was to identify any deviations from the standard declension norms of Classical Armenian (Grabar), as well as unveil the innovations of the Middle Armenian. Both nominal and pronominal declension systems have been examined. Studies show that the declension system in the colophons is not uniform. Grammatical forms of Old Armenian are used in parallel with their Middle Armenian counterparts, thus testifying to the ongoing nature of language development.
Keywords: Colophons, Classical Armenian and Middle Armenian, nominal and pronominal declension systems, irregular declension, formation of plurals